Levantamento de Neospora caninum em quatro propriedades leiteiras do município de Santana do Livramento - RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Neosporosis is a parasitary disease considered to be one of the main causes of abortion in several animals of zootechnical interest, mainly cattle, in several parts of the world. Considering the scarcity of information about the infection by this parasite in the State of Rio Grande do Sul and the fact that neosporosis is not contemplated in any governmental control program even though it is present throughout the national territory, it was aimed to study the occurrence of infection by N. caninum in dairy cows from the municipality of Sant'Anna do Livramento, located in the southern border of the State. Blood samples were collected from 40 cattle from 4 properties of the city, which were submitted to the enzyme-linked immunosorbent assay (ELISA) and were considered positive animals with an optical density greater than or equal to x2.5 the negative control serum density and intense yellow color. No animals were positive, suggesting absence of N. caninum, showing the efficiency of reproductive diseases’ control measures in the studied properties
Keywords: Bovinocultura leiteira; Ensaio Imunoenzimático; Neospora; Parasitologia; Dairy cattle; Immunoenzymatic Test; Neospora; Parasitology; CNPQ::CIENCIAS AGRARIAS